2017
DOI: 10.1177/2150131917701797
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chronic Disease Outcomes Through Medication Therapy Management in Federally Qualified Health Centers

Abstract: Introduction: Appropriate management of chronic diseases, including proper use of medications, can lead to better disease control, decrease disease-related complications, and improve overall health. Pharmacists have been shown to positively affect chronic disease outcomes through medication therapy management (MTM). The primary objectives of this project are to increase the number of patients with (1) A1c in control and (2) blood pressure in control; secondary objectives are to (3) describe number and type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…The cost of health care in the United States is the highest in the world, with total spending for 2014 reaching a new high of $3.1 trillion (18.3% of the total U.S. gross domestic product). [4][5][6][7][8] Evidence has shown that pharmacist-delivered disease state management, health promotion and disease prevention, MTM and the other aforementioned clinical services can improve patient outcomes and lower overall costs, while also alleviating the burden currently placed on the healthcare system by provider shortages and limited access to care. In 2014, 5.3% of the US population failed to obtain needed medical care due to cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of health care in the United States is the highest in the world, with total spending for 2014 reaching a new high of $3.1 trillion (18.3% of the total U.S. gross domestic product). [4][5][6][7][8] Evidence has shown that pharmacist-delivered disease state management, health promotion and disease prevention, MTM and the other aforementioned clinical services can improve patient outcomes and lower overall costs, while also alleviating the burden currently placed on the healthcare system by provider shortages and limited access to care. In 2014, 5.3% of the US population failed to obtain needed medical care due to cost.…”
Section: Introductionmentioning
confidence: 99%
“…[2] The average cost of a physician office visit is $89, while a visit to a hospital clinic or emergency department averages $245 and $406, respectively. [5][6][7][8] Many of the pharmacist-led clinical services, such as anticoagulation clinics or hypertension management programmes, are delivered in collaboration with physicians through collaborative practice agreements (CPAs), while some other services are delivered via pharmacist prescribing authority or statewide protocols such as naloxone, hormonal contraceptives, smoking cessation and immunizations. [2] There is a significant and urgent need to improve the quality, cost and accessibility of health care in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic diseases is rising, resulting in a greater health burden and increased polypharmacy with more risks for patients if therapy management and monitoring are not carried out optimally . Pharmacist intervention in the management of chronic conditions, such as in cardiovascular disease and diabetes mellitus, has the potential to ease the workload of physicians and allow them to dedicate more time to complicated cases, in the interest of patient safety and well‐being …”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist prescribing for patients with hypertension and diabetes mellitus was agreed upon by seven of the nine expert panel members and by 27 of the 31 hospital pharmacists who participated in the study. Collaborative pharmacist‐led management services in hypertension and diabetes mellitus can help to improve monitoring and control of blood pressure and blood glucose, CVD risk factors, medication adherence and optimise therapy …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation